2015
DOI: 10.1517/14712598.2015.1007039
|View full text |Cite
|
Sign up to set email alerts
|

Gene therapy in peripheral artery disease

Abstract: Compared with VEGF and FGF, HGF has a unique molecular effect on inflammation, fibrosis and cell senescence under pathological conditions. These features may explain the clinical benefits of HGF in PAD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 90 publications
0
16
0
Order By: Relevance
“…HGF, a promising biomarker for CHD, is released into the bloodstream following the damage of endothelial cells [24]. In addition, HGF has been shown to attenuate chronic tissue damage, promote angiogenesis, inhibit brosis and apoptosis, regulate in ammation and improve prognosis [25,26] in various ischemic disease models such as MI [27] and peripheral arterial occlusive disease (PAOD) [28]. The biological function of HGF is mediated by its unique tyrosine kinase receptor c-Met [29], and the activation of c-Met receptor further activates many intracellular signaling pathways including RASmitogen activated protein kinase (MAPK), signal transducer and activator of transcription (STAT), phosphatidylinositol-3 kinase (PI3K), protein kinase B (AKT), mammalian target of rapamycin (mTOR) and β-catenin pathway [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…HGF, a promising biomarker for CHD, is released into the bloodstream following the damage of endothelial cells [24]. In addition, HGF has been shown to attenuate chronic tissue damage, promote angiogenesis, inhibit brosis and apoptosis, regulate in ammation and improve prognosis [25,26] in various ischemic disease models such as MI [27] and peripheral arterial occlusive disease (PAOD) [28]. The biological function of HGF is mediated by its unique tyrosine kinase receptor c-Met [29], and the activation of c-Met receptor further activates many intracellular signaling pathways including RASmitogen activated protein kinase (MAPK), signal transducer and activator of transcription (STAT), phosphatidylinositol-3 kinase (PI3K), protein kinase B (AKT), mammalian target of rapamycin (mTOR) and β-catenin pathway [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…HGF and its potential angiogenic, anti-apoptotic, and anti-brotic effects [27,28] have been extensively studied in various models of ischaemic disease, such as MI [29] and peripheral artery occlusion disease [30]. A Phase III clinical trial of intramuscular injection of plasmid HGF for the treatment of severe limb ischaemia has been successful [31], suggesting that HGF may also be used for the treatment of IHD.…”
Section: Discussionmentioning
confidence: 99%
“…8,74 The ability to noninvasively evaluate the biodistribution of transplanted cells should be achievable through the utilization of high-sensitivity PET and SPECT imaging of radiolabeled cells (~10 4 – 10 6 cells/voxel). 75 Multiple clinical trials have already demonstrated the feasibility of tracking effective cell delivery in the myocardium of patients following myocardial infarction.…”
Section: Potential For Application Of Novel Radionuclidesmentioning
confidence: 99%
“…In addition to endovascular procedures, systemic treatments such as antiplatelet and cholesterol lowering drugs, as well as renin-angiotensin system inhibitors, have been applied for the treatment of PVD patients who are not candidates for revascularization due to multiple diffuse stenosis or arterial calcification. 8 Gene-based therapies using growth factors such as vascular endothelial growth factor (VEGF), 9 fibroblast growth factor (FGF), 10 hepatocyte growth factor (HGF), 11 and hypoxia inducible factor 1 (HIF-1) 12 have also gained attention in recent years. Additionally, cell-based therapies for PVD have been assessed using endothelial progenitor cells (EPCs), 13 bone marrow mononuclear cells (BM-MNCs), 14 and mesenchymal stem cells (MSCs) 15 and demonstrated relative benefits.…”
Section: Introductionmentioning
confidence: 99%